Corrigendum: An automatic measure for speech intelligibility in dysarthrias-validation across multiple languages and neurological disorders - Tröger, Johannes; Dörr, Felix; Schwed, Louisa; Linz, Nicklas; König, Alexandra; Thies, Tabea; Barbe, Michael T; Orozco-Arroyave, Juan Rafael; Rusz, Jan (Frontiers in digital health, 2024)
[This corrects the article DOI: 10.3389/fdgth.2024.1440986.].